Analysis of evaluation and exploratory studies on student’s resilience of online learning during pandemic of covid-19 - Dewantoro, Adi; Rachmawati, Indriyana (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
The Covid-19 pandemic has changed all systems of life, including those in the field of education. Online learning during a pandemic requires lecturers and students to learn new things that were never thought of before. Mastering technology and managing self-defence against various pressures during a pandemic are important for everyone to master. This study aims to measure the level of student resilience to online learning during the Covid-19 pandemic. This survey was conducted by distributing resilience instruments in the form of google form to students throughout the island of Java, with a total of 483 students as respondents. As many as 483 respondents who filled out the student resilience questionnaire against the Covid-19 outbreak showed that 112 respondents responded positively to online learning during the Covid-19 pandemic. Meanwhile, 371 respondents stated a negative response to online learning during the Covid-19 pandemic. Although the use of online learning models will continue with the times, it is hoped that the management of technology, pedagogy, and content in online learning can work together and provide students comfort in learning.